Acute Respiratory Failure in Bronchiolitis and Pneumonia in Infancy. Modes of Presentation and Treatment. Issue 5920 (22nd June 1974) - Simpson, H.; Matthew, D. J.; Habel, A. H.; George, E. L.
Abstract : The modes of presentation and the management of acute respiratory failure in 11 infants with severe lower respiratory tract infections (due to respiratory syncytial virus in eight) are described. Progressive respiratory difficulties leading to exhaustion, peripheral circulatory collapse, recurrent apnoeic attacks, or generalized convulsions were the main clinical presentations resulting in severe ventilatory failure. In nine infants preventilation carbon dioxide tensions exceeded 65 mm Hg. It seems likely that the use of intermittent positive-pressure ventilation in these patients contributed to the low mortality rate, less than 0·5%, from such illnesses during the 15-month study period.